2010
DOI: 10.1007/s11104-010-0343-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and architectural development of root systems in sorghum and maize

Abstract: Root systems determine the capacity of a plant to access soil water and their architecture can influence adaptation to water-limited conditions. It may be possible to associate that architecture with root attributes of young plants as a basis for rapid phenotypic screening. This requires improved understanding of root system development. This study aimed to characterise the morphological and architectural development of sorghum and maize root systems by (i) clarifying the initiation and origin of roots at germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
125
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 52 publications
2
125
0
4
Order By: Relevance
“…The use of the surface organic mulch diminishes soil temperature due to low thermal conductivity (Khan et al, 2000), favourably influences the water content by controlling evaporation from the soil surface and absorbing water vapour onto mulch tissue (Mulumba and Lal, 2008;Sekhon et al, 2010), and aggregation of soil particles (Jordan et al, 2010; Kêsik et al, 2010) affects the quantity of rainwater entering the soil and evaporation (Ghosh et al, 2006) and crop yield (Siczek and Lipiec, 2011). Furthermore, mulch significantly increases symbiotic nitrogen fixation as measured by nitrogenase activity, nodule diameter, and dry weight (Siczek and Lipiec, 2011).…”
Section: Soil Management and Irrigationmentioning
confidence: 99%
“…The use of the surface organic mulch diminishes soil temperature due to low thermal conductivity (Khan et al, 2000), favourably influences the water content by controlling evaporation from the soil surface and absorbing water vapour onto mulch tissue (Mulumba and Lal, 2008;Sekhon et al, 2010), and aggregation of soil particles (Jordan et al, 2010; Kêsik et al, 2010) affects the quantity of rainwater entering the soil and evaporation (Ghosh et al, 2006) and crop yield (Siczek and Lipiec, 2011). Furthermore, mulch significantly increases symbiotic nitrogen fixation as measured by nitrogenase activity, nodule diameter, and dry weight (Siczek and Lipiec, 2011).…”
Section: Soil Management and Irrigationmentioning
confidence: 99%
“…There has been limited work on roots in sorghum, except recent report by Singh et al (2010), and until recently this work has been restricted to a morphological evaluation of a limited number of genotypes. For instance, several studies have shown genotypic variations for rooting traits in genotypes contrasting for drought tolerance (Blum et al, 1977;Abd-Ellatif et al, 1978;Jordan et al, 1979;Vadez et al, 2007a).…”
mentioning
confidence: 99%
“…Gelukkig is er diversiteit in koudetolerantie, wat mogelijkheden biedt voor veredeling voor hoger gelegen regio's en hogere breedtegraden. Sorghum is een C4-plant evenals bijvoorbeeld (snij)maïs, maar gaat veel efficiënter om met water (Reddy et al, 2011;Premachandra et al, 1994;Singh et al, 2010;Robertson et al, 1993 ). Ze is goed bestand tegen veel regen en goed aangepast aan hoge zonnestraling en hoge temperaturen.…”
Section: Milieuomstandighedenunclassified